Applying cognitive-social theory to health-protective behavior Breast self-examination in cancer screening. [article]. - Collins, Rebecca L.
Applies recent developments in cognitive-social theory to health-protective behavior, articulating a Cognitive-Social Health Information Processing (C-SHIP) model. This model of the genesis and maintenance of health-protective behavior focuses on the individual's encodings and construals, expectancies, affects, goals and values, self-regulatory competencies, and their interactions with each other and the health-relevant information in the course of cognitive-affective processing. In processing health information, individuals are assumed to differ in both the accessibility of these mental representations and the organization of relationships among them. In this article, the model is applied to analyze and integrate the often-confusing findings on breast self-examination in cancer screening. Implications are considered for assessments and interventions to enhance adherence to complex, long-term, health-protective regimens, tailored to the needs and characteristics of the individual. -- (from the author)